Sports preparticipation examination to screen college athletes for chlamydia trachomatis - Hennrikus, E.; Oberto, D.; Linder, J. M.; Rempel, J. M. L.; Hennrikus, N. (Medicine & Science in Sports & Exercise, 2010)
Purpose: This study assessed the prevalence of Chlamydia trachomatis in the college athlete and the benefit of using the sports preparticipation examination (PPE) as a screening opportunity. Methods: Chlamydia teaching and screening was part of the sports PPE. The 439 athletes (220 men and 219 women) answered a questionnaire and provided urine specimens. Using positive test results as an indication of prevalence, the chlamydia prevalence rate was calculated by sex and race. Using the questionnaire responses, we determined the students' accessibility to health care and the percentage of sexually active students who were ever offered chlamydial screening. Results: Thirteen of 439 athletes tested positive. One test was a false positive. The test positivity was 2.7%: 3.2% men and 2.2% women. In sexually active athletes, the test positivity rose to 3.8%: 4.0% men and 3.7% women. African American athletes had a higher prevalence of 9.1%: 8.9% in men and 9.5% in women, making them six times more likely to have chlamydia than Caucasian athletes (odds ratio = 6.43, 95% confidence interval = 1.58-30.55). Number of partners, contraceptive type, symptoms, and prior history of chlamydia were not statistically different between groups. Over 75% of students saw their private physicians, yet of the sexually active students, only 31% of women and 6.8% of men were ever offered chlamydial screening. Conclusions: The Centers for Disease Control and Prevention and the U.S. Preventive Services Task Force guidelines recommending annual chlamydial screening for all sexually active women younger than 26 yr are not being met in the community. Taking advantage of opportunities, including the mandated sports PPE, where sexually active men and women 25 yr and younger interface with the health care system to screen for C. trachomatis, is crucial to decreasing the continued rise of chlamydial infection.